2005
DOI: 10.1246/bcsj.78.95
|View full text |Cite
|
Sign up to set email alerts
|

Redox Properties and Basicity of Keggin-Type Polyoxometalate Complexes

Abstract: For Keggin-type polyoxometalate complexes (α-[XMo12O40]n− (X = S, P, As, Si, Ge; n = 2–4) and α-[XW12O40]n− (X = S, P, As, Si, Ge, B, Al; n = 2–5)), the conversion processes of the first two one-electron waves into a two-electron wave were investigated in dipolar aprotic solvents containing H+, Li+, or Na+ as a Lewis acid. A simulation of the cyclic voltammogram indicated that the potential difference (ΔEmid) between the first one- and two-electron redox waves served as a useful criterion for the basicity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 22 publications
7
47
0
Order By: Relevance
“…This further documents the expectation that the analogous [SiW 12 O 40 ] 4À/5À/6À/7À/8À sequence could be expected in water if a wider potential range were available. The E 00 values obtained from cyclic voltammograms ( Table 6) are in good agreement with those reported in the literature [7,27,28]. The separation of potentials for processes I and II, and III and IV are similar, further supporting the value of E 00 for the [SiW 12 O 40 ] 7À/8À process in water (assumed above for the simulation of that process).…”
Section: Cyclic Voltammograms Of [A-siw 12 O 40 ] 4à In Buffered Aquesupporting
confidence: 88%
See 2 more Smart Citations
“…This further documents the expectation that the analogous [SiW 12 O 40 ] 4À/5À/6À/7À/8À sequence could be expected in water if a wider potential range were available. The E 00 values obtained from cyclic voltammograms ( Table 6) are in good agreement with those reported in the literature [7,27,28]. The separation of potentials for processes I and II, and III and IV are similar, further supporting the value of E 00 for the [SiW 12 O 40 ] 7À/8À process in water (assumed above for the simulation of that process).…”
Section: Cyclic Voltammograms Of [A-siw 12 O 40 ] 4à In Buffered Aquesupporting
confidence: 88%
“…In the case of [PW 12 O 40 ] 3À , Himeno et al added perchloric acid, to provide a situation where processes II and III when combined with acid-base chemistry become coincident in CH 3 CN [7]. The voltammetry in acidic CH 3 CN solution was simulated assuming reaction Scheme 7.…”
Section: Cyclic Voltammograms Of [A-siw 12 O 40 ] 4à In Buffered Aquementioning
confidence: 99%
See 1 more Smart Citation
“…For anhydrous H3PW12O40, the protons have been reported to be attached to the most basic bridging oxygen atoms based on infrared (IR) and 17 O NMR spectroscopy results [21]. Himeno and co-workers reported that the potential difference between the first one-and two-electron redox waves of cyclic voltammograms served as a useful criterion for the basicity of Keggin anions [85,86] …”
Section: Heteropolyoxometalatesmentioning
confidence: 99%
“…Several researches on the redox nature of HPAs have been conducted through theoretical and experimental studies such as DFT calculation [4], electrochemical measurement [5][6][7][8], UV-visible spectroscopy [8][9][10], and scanning tunneling microscopy [11]. Due to the diversity of mixed-addenda HPAs, however, much progress has not been made on the redox behavior of Wells-Dawson tungstoarsenates.…”
Section: Introductionmentioning
confidence: 99%